Association between PD1 mRNA and response to anti-PD1 monotherapy across multiple cancer types. (27th August 2018) - Paré, L; Pascual, T; Seguí, E; Teixidó, C; Gonzalez-Cao, M; Galván, P; Rodríguez, A; González, B; Cuatrecasas, M; Pineda, E; Torné, A; Crespo, G; et al.
Abstract: Background: We hypothesized that the abundance of PD1 mRNA in tumor samples might explain the differences in overall response rates (ORR) observed following anti-PD1 monotherapy across cancer types. Patients and methods: RNASeqv2 data from 10 078 tumor samples representing 34 different cancer types was analyzed from TCGA. Eighteen immune-related gene signatures and 547 immune-related genes, including PD1, were explored. Correlations between each gene/signature and ORRs reported in the literature following anti-PD1 monotherapy were calculated. To translate the in silico findings to the clinical setting, we analyzed the expression of PD1 mRNA using the nCounter platform in 773 formalin-fixed paraffin embedded (FFPE) tumor samples across 17 cancer types. To test the direct relationship between PD1 mRNA, PDL1 immunohistochemistry (IHC), stromal tumor-infiltrating lymphocytes (sTILs) and ORR, we evaluated an independent FFPE-based dataset of 117 patients with advanced disease treated with anti-PD1 monotherapy. Results: In pan-cancer TCGA, PD1 mRNA expression was found strongly correlated ( r  > 0.80) with CD8 T-cell genes and signatures and the proportion of PD1 mRNA-high tumors (80th percentile) within a given cancer type was variable (0%–84%). Strikingly, the PD1 -high proportions across cancer types were found strongly correlated ( r  = 0.91) with the ORR following anti-PD1 monotherapy reported in the literature. Lower correlations were found with other immune-related genes/signatures, including PDL1 . Using the same population-based cutoff (80 th percentile), similar proportions of PD1 -high disease in a given cancer type were identified in our in-house 773 tumor dataset as compared with TCGA. Finally, the pre-established PD1 mRNA FFPE-based cutoff was found significantly associated with anti-PD1 response in 117 patients with advanced disease ( PD1 -high 51.5%, PD1 -intermediate 26.6% and PD1 -low 15.0%; odds ratio between PD1 -high and PD1 -intermediate/low = 8.31; P  < 0.001). In this same dataset, PDL1 tumor expression by IHC or percentage of sTILs was not found associated with response. Conclusions: Our study provides a clinically applicable assay that links PD1 mRNA abundance, activated CD8 T-cells and anti-PD1 efficacy.